Preparation method and application of polyacid supported MOFs composite catalyst
By designing a multi-acid-supported MOFs composite catalyst, the porous structure of MOFs and the electron sponge characteristics of polyacids are used to construct a heterojunction structure, which solves the problem of the fast charge recombination rate of MOFs during photocatalytic degradation, and achieves efficient photocatalytic degradation effect.
Patent Information
- Application Number
- CN202411871355.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
When used in the degradation of neonicotinic insecticides, the microbial degradation efficiency is limited by environmental conditions, and the biochar adsorption effect is affected by preparation conditions. Although chemical oxidation method is efficient, it has a great impact on the environment. The charge recombination rate of MOFs during photocatalytic degradation is too fast, and the high band gap value limits the utilization of visible light.
A polyacid-supported MOFs composite catalyst is designed. By heating Zr salt and benzoic acid in N,N-dimethylformamide, H4TBAPy and trifluoroacetic acid are added, and after reaction, it is compounded with Ni4P2-POM to form a composite catalyst. The porous structure of MOFs and the electron sponge characteristics of polyacids are used to construct a heterojunction structure to enhance the migration of photogenerated electrons and holes.
The photocatalytic activity of the composite catalyst is improved, and the effect of stable performance, high catalyticity and recyclable use is achieved, which reduces the impact of high temperature and high pressure conditions on the polyacid and MOFs structures, ensuring the performance characteristics of the catalyst.
Smart Images

Figure CN119680647A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite catalysts, and in particular to a preparation method and application of a polyacid-supported MOFs composite catalyst. Background Art
[0002] In recent years, with the widespread use of pesticides such as neonicotinoids, they have accumulated seriously in groundwater and surface water, and eventually entered the food chain, posing a serious threat to human health and environmental safety. The methods commonly used to degrade neonicotinoids include microbial degradation, biochar adsorption and chemical oxidation. Among them, the microbial degradation method mainly uses some microorganisms in the soil, water and other environments, such as bacteria and fungi, to metabolize and decompose neonicotinoid pesticides as carbon sources or nitrogen sources, thereby degrading pesticides; however, the growth and metabolic activities of microorganisms have strict requirements on environmental conditions, and in the natural environment, conditions such as temperature, pH and humidity are not always in the most favorable state for microbial degradation, thus affecting the degradation efficiency. Moreover, different microorganisms have different degradation abilities for different types of neonicotinoid pesticides. A microorganism may only be able to degrade a few specific pesticides. For complex pesticide-contaminated environments, the degradation effect of a single microorganism is often limited. The biochar adsorption method uses the adsorption of biochar to help remove neonicotinoid pesticide molecules from the environment, and uses the reaction between the surface functional groups of biochar and pesticides to promote the degradation of pesticides. However, the adsorption and degradation effects of biochar are affected by factors such as preparation raw materials, pyrolysis temperature, and residence time, and the material requirements are strict. The chemical oxidation method uses strong oxidizing properties to degrade and transform organic pollutants in pesticides through redox reactions. This method is less affected by the environment and removes pesticides efficiently and thoroughly.
[0003] Metal-organic framework (MOFs) compounds have a large specific surface area and porous structure, which not only provides abundant active sites for photocatalytic reactions, but also enables substrate molecules to quickly diffuse to the active center of the catalyst, increasing the contact opportunities between the substrate and the catalyst, thereby improving the efficiency of the photocatalytic reaction. However, some MOFs materials have problems such as few reactive active sites and difficulty in separating electrons and holes, resulting in low photocatalytic efficiency; in addition, commonly used MOFs materials have a high band gap value, which limits the utilization of visible light, thereby affecting the photocatalytic efficiency.
[0004] In view of this, it is necessary to design an improved preparation method of polyacid-supported MOFs composite catalyst and its application to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method of a polyacid-supported MOFs composite catalyst and its application.
[0006] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing a polyacid-supported MOFs composite catalyst, comprising the following steps:
[0007] Disperse Zr salt and benzoic acid in N,N-dimethylformamide, heat at 100°C for 1h, add H4TBAPy and trifluoroacetic acid to the reaction solution, mix well, react at 100°C for 18h, and after the reaction, centrifuge and wash the reaction solution to obtain NU-1000;
[0008] Under stirring conditions, an aqueous solution of Ni(OOCCH3)2 is slowly added to a mixed solution of Na2WO4·2H2O and Na2HPO4 to obtain a mixture; the mixture is refluxed for 2.5 hours, and after filtering the precipitate, K(OOCCH3) is added to the filtrate to obtain Ni4P2-POM;
[0009] NU-1000 was added to the aqueous solution of Ni4P2-POM, and the mixture was reacted at 25°C for 72 hours under stirring to obtain a composite catalyst.
[0010] Preferably, the ratio of the content of Ni4P2-POM in the aqueous solution of Ni4P2-POM to the added amount of NU-1000 is (1-5):1.
[0011] Preferably, the ratio of the mass of Zr salt, the mass of benzoic acid, and the volume of N,N-dimethylformamide is 0.098 g:2 g:8 mL.
[0012] Preferably, the ratio of the mass of H4TBAPy to the volume of trifluoroacetic acid is 0.04 g:40 μL.
[0013] Preferably, the ratio of the solute mass to the solvent volume in the aqueous solution of Ni(OOCCH3)2 is 5.5g:50mL.
[0014] Preferably, the pH of the mixed solution is 7.0.
[0015] Preferably, the mixed solution is obtained by dissolving 33 g Na2WO4·2H2O and 1.57 g Na2HPO4 in 100 mL water.
[0016] Preferably, the added amount of K(OOCCH3) is 4 g.
[0017] On the other hand, the present invention also provides a composite catalyst, which has a regular hexahedral rod-like structure and a specific surface area of 392.59-690.79 m 2 / g, total pore volume is 0.2150-0.3646cm 3 / g, and it can be applied to the photocatalytic degradation of pesticide organic pollutants.
[0018] The beneficial effects of the present invention are:
[0019] 1. The preparation method of the polyacid-supported MOFs composite catalyst provided by the present invention is to prepare the composite catalyst by first preparing the polyacid and MOFs separately, and then compounding the polyacid and MOFs, which can give full play to the structural characteristics of MOFs (porous structure) and the performance characteristics of the polyacid (electronic sponge characteristics) to realize the compounding of the two. The compounding process of the polyacid and MOFs can construct a heterojunction structure in the composite catalyst to enhance the migration of photogenerated electrons and holes, solve the problem of too fast charge recombination rate of MOFs when used for photocatalytic degradation, thereby enhancing the photocatalytic activity of the composite catalyst, and obtain a composite catalyst with stable performance, high catalyticity and recyclable use. In the above manner, a preparation method of a polyacid-supported MOFs composite catalyst with simple preparation and mild preparation conditions is provided.
[0020] 2. The preparation method of the polyacid-loaded MOFs composite catalyst provided by the present invention can realize the composite of polyacid and MOFs at room temperature, reducing the influence of high temperature and high pressure conditions on the structure of polyacid and MOFs, ensuring that the composite catalyst retains the performance characteristics of polyacid and MOFs to the greatest extent, and giving the composite catalyst excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The XRD diagrams of the composite catalysts prepared in Examples 1 to 3 of the present invention;
[0022] Figure 2 IR graphs of the composite catalysts prepared in Examples 1 to 3 of the present invention;
[0023] Figure 3 The SEM images and EDS-mapping images of the composite catalysts prepared in Examples 1 to 3 of the present invention;
[0024] Figure 4 The XPS graphs of the composite catalysts prepared in Examples 1 to 3 of the present invention;
[0025] Figure 5 The photoelectric properties of the composite catalysts prepared in Examples 1 to 3 of the present invention;
[0026] Figure 6 The diagram is a mechanism diagram of the composite catalysts prepared in Examples 1 to 3 of the present invention forming a heterojunction structure;
[0027] Figure 7 The photocatalytic degradation diagram of the composite catalyst prepared in Examples 1 to 3 of the present invention;
[0028] Figure 8This is a photocatalytic degradation cycle result diagram of the composite catalyst prepared in Example 2 of the present invention;
[0029] Fig. 9 for Figure 7 XRD and IR patterns of the composite catalyst before and after the medium photodegradation cycle experiment;
[0030] Fig.10 for Figure 7 EDS-mapping diagram of the composite catalyst after the medium photodegradation cycle experiment. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0033] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0034] The preparation method of the polyacid-supported MOFs composite catalyst provided by the present invention comprises the following steps:
[0035] Preparation of the organic metal framework compound NU-1000: Zr salt and benzoic acid are dispersed in N,N-dimethylformamide, and heated at 100°C for 1 hour. After heating, H4TBAPy and trifluoroacetic acid are added to the reaction solution, mixed evenly, and reacted at 100°C for 18 hours. After the reaction, the reaction solution is centrifuged and washed to obtain NU-1000;
[0036] [Ni4(H2O)2(PW9O 34 )2] 10- Preparation of (Ni4P2): Under stirring conditions, an aqueous solution of Ni(OOCCH3)2 is slowly added to a mixed solution of Na2WO4·2H2O and Na2HPO4 to obtain a mixture; the mixture is refluxed for 2.5 h, and after filtering the precipitate, K(OOCCH3) is added to the filtrate to obtain Ni4P2-POM;
[0037] Preparation of composite catalyst: NU-1000 was added to the aqueous solution of Ni4P2-POM, and the mixture was stirred at 25°C for 72 hours. After the reaction, the product was washed and dried to obtain the composite catalyst. The composite catalyst was in the form of a regular hexahedral rod, and its specific surface area was 392.59-690.79 m 2 / g, total pore volume is 0.2150-0.3646cm 3 / g.
[0038] In the above technical scheme, by combining polyacids and MOFs to prepare the catalyst, the structural characteristics of MOFs (porous structure) and the performance characteristics of polyacids (electronic sponge characteristics) can be fully utilized to achieve the combination of the two. In this process, the pore structure of MOFs can be used to stabilize the polyacid, which can not only avoid the agglomeration of the polyacid, but also ensure the stability of the composite catalyst; secondly, the composite process of polyacids and MOFs can construct a heterojunction structure in the composite catalyst to enhance the migration of photogenerated electrons and holes, solve the problem of too fast charge recombination rate of MOFs when used for photocatalytic degradation, thereby enhancing the photocatalytic activity of the composite catalyst; furthermore, the above-mentioned composite process of polyacids and MOFs can be achieved at room temperature. On the one hand, it solves the defect of strict requirements on preparation conditions when preparing polyacids and MOFs by traditional methods, reducing the difficulty of preparation. On the other hand, it reduces the influence of high temperature and high pressure conditions on the structure of polyacids and MOFs, ensuring that the composite catalyst retains the performance characteristics of polyacids and MOFs to the greatest extent.
[0039] In some embodiments, when preparing a composite catalyst, the ratio of the content of Ni4P2-POM in the aqueous solution of Ni4P2-POM to the added amount of NU-1000 is (1-5):1; by controlling the added amounts of polyacid and MOFs within the above range, when the polyacid is loaded in the pore structure of MOFs, it is possible to ensure that the polyacid is uniformly dispersed in the pore structure of MOFs, and avoid agglomeration of the polyacid to affect the overall performance of the catalyst.
[0040] In particular, the composite catalyst prepared by the present invention can be applied to the photocatalytic degradation of organic pollutants in pesticides, and applicable pesticides include neonicotinoids, etc., especially thiamethoxam (TMX).
[0041] The preparation method and application of the polyacid-supported MOFs composite catalyst of the present invention are further described below in conjunction with specific embodiments:
[0042] Example 1
[0043] This embodiment prepares a polyacid-supported MOFs composite catalyst, and the preparation method thereof comprises the following steps:
[0044] Preparation of the organometallic framework compound NU-1000: 0.098 g ZrOCl2·8H2O and 2 g benzoic acid (Chinese medicine, analytical grade) were dispersed in 8 mL N,N-dimethylformamide (Chinese medicine, analytical grade) and heated at 100°C for 1 h. After heating, the reaction system was cooled to room temperature. Then, 0.04 g H4TBAPy and 40 μL trifluoroacetic acid (Chinese medicine, analytical grade) were mixed evenly, ultrasonicated for 20 minutes, and reacted at 100°C for 18 hours. After the reaction, the reaction solution was centrifuged and washed three times with N,N-dimethylformamide to obtain a yellow crystalline material; the yellow crystals were soaked in fresh N,N-dimethylformamide for 2 hours, and centrifuged to obtain a yellow powder after the soaking; then, 12 mL N,N-dimethylformamide and 0.5 mL 8M hydrochloric acid aqueous solution were added to the yellow powder, and the resulting mixture was reacted at 100°C for 18 hours. After the reaction, it was washed three times with N,N-dimethylformamide; finally, after soaking in acetone (Chinese medicine, analytical grade) for 12 hours, NU-1000 crystals were collected by centrifugation, and dried and activated in a vacuum oven at 80°C overnight;
[0045] [Ni4(H2O)2(PW9O 34 )2] 10- Preparation of (Ni4P2): 33g Na2WO4·2H2O and 1.57g Na2HPO4 were dissolved in 100mL water, and the pH value was adjusted to 7.0 with acetic acid to obtain a mixed solution of Na2WO4·2H2O and Na2HPO4; 5.5g Ni(OOCCH3)2·4H2O was dissolved in 50mL ultrapure water to obtain an aqueous solution of Ni(OOCCH3)2; under stirring, the aqueous solution of Ni(OOCCH3)2 was slowly added to the above mixed solution to obtain a mixture; the mixture was refluxed for 2.5h, hot filtered to remove the precipitate, 4g K(OOCCH3) was added to the filtrate, and yellow crystals were obtained after cooling and crystallization; finally, it was filtered to obtain Ni4P2-POM;
[0046] Preparation of composite catalyst: 100 mg Ni4P2-POM was completely dissolved in 40 mL deionized water, 100 mg NU-1000 was added to the resulting solution, and after ultrasonic treatment for 20 min, the mixture was reacted at 25 °C for 72 h under stirring. After the reaction, the product was washed with deionized water for 3 times and dried at 60 °C under vacuum for 12 h to obtain a composite catalyst named 0.1-Ni4P2@NU-1000 with a specific surface area of 690.79 m 2 / g, and the total pore volume is 0.3646 cm 3It should be noted that, unless otherwise specified, the reagents used in the present invention can be purchased from the market.
[0047] Example 2
[0048] This embodiment prepares a polyacid-supported MOFs composite catalyst, and the preparation method thereof comprises the following steps:
[0049] Preparation of the organometallic framework compound NU-1000: 0.098 g ZrOCl2·8H2O and 2 g benzoic acid (Chinese medicine, analytical grade) were dispersed in 8 mL N,N-dimethylformamide (Chinese medicine, analytical grade) and heated at 100°C for 1 h. After heating, the reaction system was cooled to room temperature. Then, 0.04 g H4TBAPy and 40 μL trifluoroacetic acid (Chinese medicine, analytical grade) were mixed evenly, ultrasonicated for 20 minutes, and reacted at 100°C for 18 hours. After the reaction, the reaction solution was centrifuged and washed three times with N,N-dimethylformamide to obtain a yellow crystalline material; the yellow crystals were soaked in fresh N,N-dimethylformamide for 2 hours, and centrifuged to obtain a yellow powder after the soaking; then, 12 mL N,N-dimethylformamide and 0.5 mL 8M hydrochloric acid aqueous solution were added to the yellow powder, and the resulting mixture was reacted at 100°C for 18 hours. After the reaction, it was washed three times with N,N-dimethylformamide; finally, after soaking in acetone (Chinese medicine, analytical grade) for 12 hours, NU-1000 crystals were collected by centrifugation, and dried and activated in a vacuum oven at 80°C overnight;
[0050] [Ni4(H2O)2(PW9O 34 )2] 10- Preparation of (Ni4P2): 33g Na2WO4·2H2O and 1.57g Na2HPO4 were dissolved in 100mL water, and the pH value was adjusted to 7.0 with acetic acid to obtain a mixed solution of Na2WO4·2H2O and Na2HPO4; 5.5g Ni(OOCCH3)2·4H2O was dissolved in 50mL ultrapure water to obtain an aqueous solution of Ni(OOCCH3)2; under stirring, the aqueous solution of Ni(OOCCH3)2 was slowly added to the above mixed solution to obtain a mixture; the mixture was refluxed for 2.5h, hot filtered to remove the precipitate, 4g K(OOCCH3) was added to the filtrate, and yellow crystals were obtained after cooling and crystallization; finally, it was filtered to obtain Ni4P2-POM;
[0051] Preparation of composite catalyst: 300 mg Ni4P2-POM was completely dissolved in 40 mL deionized water, 100 mg NU-1000 was added to the resulting solution, and after ultrasonic treatment for 20 min, the mixture was reacted at 25 °C for 72 h under stirring. After the reaction, the product was washed with deionized water for 3 times and dried at 60 °C under vacuum for 12 h to obtain a composite catalyst named 0.3-Ni4P2@NU-1000 with a specific surface area of 530.15 m 2 / g, and the total pore volume is 0.2767cm 3 / g.
[0052] Example 3
[0053] This embodiment prepares a polyacid-supported MOFs composite catalyst, and the preparation method thereof comprises the following steps:
[0054] Preparation of the organometallic framework compound NU-1000: 0.098 g ZrOCl2·8H2O and 2 g benzoic acid (Chinese medicine, analytical grade) were dispersed in 8 mL N,N-dimethylformamide (Chinese medicine, analytical grade) and heated at 100°C for 1 h. After heating, the reaction system was cooled to room temperature. Then, 0.04 g H4TBAPy and 40 μL trifluoroacetic acid (Chinese medicine, analytical grade) were mixed evenly, ultrasonicated for 20 minutes, and reacted at 100°C for 18 hours. After the reaction, the reaction solution was centrifuged and washed three times with N,N-dimethylformamide to obtain a yellow crystalline material; the yellow crystals were soaked in fresh N,N-dimethylformamide for 2 hours, and centrifuged to obtain a yellow powder after the soaking; then, 12 mL N,N-dimethylformamide and 0.5 mL 8M hydrochloric acid aqueous solution were added to the yellow powder, and the resulting mixture was reacted at 100°C for 18 hours. After the reaction, it was washed three times with N,N-dimethylformamide; finally, after soaking in acetone (Chinese medicine, analytical grade) for 12 hours, NU-1000 crystals were collected by centrifugation, and dried and activated in a vacuum oven at 80°C overnight;
[0055] [Ni4(H2O)2(PW9O 34 )2] 10-Preparation of (Ni4P2): 33g Na2WO4·2H2O and 1.57g Na2HPO4 were dissolved in 100mL water, and the pH value was adjusted to 7.0 with acetic acid to obtain a mixed solution of Na2WO4·2H2O and Na2HPO4; 5.5g Ni(OOCCH3)2·4H2O was dissolved in 50mL ultrapure water to obtain an aqueous solution of Ni(OOCCH3)2; under stirring, the aqueous solution of Ni(OOCCH3)2 was slowly added to the above mixed solution to obtain a mixture; the mixture was refluxed for 2.5h, hot filtered to remove the precipitate, 4g K(OOCCH3) was added to the filtrate, and yellow crystals were obtained after cooling and crystallization; finally, it was filtered to obtain Ni4P2-POM;
[0056] Preparation of composite catalyst: 500 mg Ni4P2-POM was completely dissolved in 40 mL deionized water, 100 mg NU-1000 was added to the resulting solution, and after ultrasonic treatment for 20 min, the mixture was reacted at 25 °C for 72 h under stirring. After the reaction, the product was washed with deionized water for 3 times and dried at 60 °C under vacuum for 12 h to obtain a composite catalyst named 0.5-Ni4P2@NU-1000 with a specific surface area of 392.59 m 2 / g, and the total pore volume is 0.2150cm 3 / g.
[0057] The XRD patterns of the composite catalysts prepared in Examples 1 to 3, Ni4P2-POM and NU-1000 are as follows: Figure 1 As shown in Figure 2, after analysis, the characteristic peaks corresponding to Ni4P2-POM did not appear in the spectra of the three composite catalysts, indicating that Ni4P2-POM was distributed inside the pores of NU-1000; the FT-IR images of the three composite catalysts and Ni4P2-POM are shown in Figure 2. Figure 2 As shown in the figure, the three composite catalysts have -1 and 750-1100cm -1 Vibration peaks were observed in the range of 1615 cm -1 、1520cm -1 and 1417cm -1 The peak at 1040 cm corresponds to the -COOH stretching vibration of NU-1000. -1 、963cm -1 and 886cm -1The peak at corresponds to the stretching vibration of WO and PO in Ni4P2-POM, and in the composite catalyst, characteristic peaks belonging to Ni4P2-POM and NU-1000 are observed, indicating that Ni4P2-POM is successfully loaded on NU-1000; the SEM images of NU-1000 and 0.3-Ni4P2@NU-1000 are shown in Figure 2. Figure 3 (a) and Figure 3 (b) from Figure 3 (a) It can be seen that NU-1000 has a regular hexahedral rod structure. By comparing the two figures, it can be found that the loading of Ni4P2-POM has no obvious effect on the morphology and surface smoothness of NU-1000; the EDS-mapping diagram of 0.3-Ni4P2@NU-1000 is shown in Figure 3 As shown in (c)-(i), it can be seen from the figure that Zr, O, C, P, W, and Ni elements are evenly distributed in the entire structure, indicating that Ni4P2 is evenly distributed inside the pores of NU-1000 without agglomeration. The XPS image of 0.3-Ni4P2@NU-1000 is shown in Figure 4 As shown in the figure, it can be seen that Zr, O, C, P, W, and Ni elements exist simultaneously in the composite catalyst. This conclusion further verifies the successful preparation of the composite catalyst 0.3-Ni4P2@NU-1000.
[0058] Furthermore, the present invention also uses ultraviolet-visible spectroscopy (UV-vis) to evaluate the optical properties of the composite catalyst. Figure 5 As shown in a, it can be seen from the figure that compared with NU-1000, the absorption curves of the three composite catalysts in Examples 1-3 have a red shift, among which 0.3-Ni4P2@NU-1000 shifts to a longer wavelength, indicating that the introduction of Ni4P2-POM effectively enhances the visible light response ability of the composite catalyst, thereby improving its photocatalytic activity.
[0059] Using the Tauc plot equation (αhv) 2 =A(hv-Eg) The band gap values of each catalyst were calculated. The E of NU-1000, Ni4P2-POM, 0.1-Ni4P2@NU-1000, 0.3-Ni4P2@NU-1000 and 0.5-Ni4P2@NU-1000 g The values are 2.52eV, 2.47eV, 2.50eV, 2.45eV, and 2.48eV, respectively. The MS curves of NU-1000 and Ni4P2-POM at different frequencies are shown in Figure 2. Figure 5 b, 5c, the flat band potential (E FB ) are -0.88 and -0.61 V (relative to Ag / AgCl), respectively. According to the formula E NHE=E Ag / AgCl +0.197, the E of NU-1000 and Ni4P2-POM can be calculated. FB The slopes of NU-1000 and Ni4P2-POM are positive, so they are both n-type semiconductors. FB Conduction band (E CB ) is positive 0.1eV, so the E of NU-1000 and Ni4P2-POM CB are -0.78 and -0.51 eV, respectively. Therefore, the E VB 1.74 and 1.96 eV respectively, and the valence band (E VB ) can be obtained by formula E VB =E CB +E g The fluorescence intensity of 0.3-Ni4P2@NU-1000 is weaker than that of NU-1000, indicating that the photogenerated electron-hole separation rate of 0.3-Ni4P2@NU-1000 is higher ( Figure 5 d). Photocurrent response Figure 5 As shown in Figure e, the photocurrent intensity of 0.3-Ni4P2@NU-1000 is 2.1, 1.3 and 0.1 times that of NU-1000, 0.1-Ni4P2@NU-1000 and 0.5-Ni4P2@NU-1000 respectively. Figure 5 f), 0.3-Ni4P2@NU-1000 has the smallest arc radius, indicating that its impedance is the smallest. According to the above photoelectric test results and XPS test results, it can be determined that Ni4P2-POM and NU-1000 form a Z-type heterojunction structure, such as Figure 6 As shown. Under the action of visible light, the electrons on the valence bands of Ni4P2-POM and NU-1000 are excited to their own conduction bands respectively. In addition, since NU-1000 has a more negative conduction band than Ni4P2-POM, the electrons flow from Ni4P2-POM to NU-1000, thus forming a Z-type heterojunction structure.
[0060] The photocatalytic activity of the composite catalyst was evaluated by evaluating the degradation of TMX under visible light irradiation. The specific experimental method was as follows: 100 mL of TMX solution was mixed with 10 mg of catalyst, and dark adsorption was first performed in a dark environment under magnetic stirring conditions, and dark adsorption equilibrium was reached after 60 min of adsorption; then, the mixed solution that reached dark adsorption equilibrium was placed under a 300 W xenon lamp to cause a photocatalytic reaction, 3 mL of the reaction solution was taken out at regular intervals, and the absorbance of the solution at 250 nm was tested using a UV-visible spectrophotometer. All degradation experiments were repeated three times, and the standard deviation was calculated; degradation rate (%) = (1-A / A0) × 100%, where A0 represents the initial concentration of TMX, and A represents the concentration of TMX at a certain moment. The experimental results are shown in FIG. Figure 7 As shown in the figure, it can be seen that in the blank group (without catalyst), TMX is almost not degraded after 120 minutes of visible light irradiation; and pure NU-1000 has no degradation ability for TMX after reaching adsorption-desorption equilibrium; under the same conditions, the photodegradation efficiency of TMX by 0.1-Ni4P2@NU-1000, 0.3-Ni4P2@NU-1000 and 0.5-Ni4P2@NU-1000 is 72.7%, 75.1% and 72.5%, respectively. In addition, with the increase of Ni4P2-POM content, the degradation rate of TMX shows a trend of first increasing and then decreasing. This is mainly due to the following reasons: pure NU-1000 has a higher band gap value and is not sensitive to visible light. The utilization rate is low, and its photogenerated electrons and holes are easily aggregated, resulting in a fast charge recombination rate, which will also affect the photocatalytic efficiency; and pure Ni4P2-POM has a limited number of catalytic active sites available on the surface. When faced with high concentrations or large amounts of pollutants to be degraded, it is difficult to achieve an ideal treatment effect in a short time, and most pure POMs mainly absorb ultraviolet light, have poor utilization of visible light, and have low photocatalytic degradation efficiency. When an appropriate amount of NU-1000 and Ni4P2-POM are compounded, the above defects can be effectively solved and the photocatalytic degradation performance of NU-1000 and Ni4P2-POM can be fully exerted, but excessive loading of Ni4P2-POM will hinder the contact between the substrate (TMX) and the active sites. The TMX solution is prepared as follows: 100 mg TMX is dissolved in 100 mL pure water and then transferred to a 1000 mL volumetric flask and fixed to volume. The solution is used as the mother solution for photocatalytic degradation. During photocatalytic degradation, 10 mL of the mother solution is accurately measured using a pipette and fixed to volume in a 100 mL volumetric flask. The resulting solution is used for photocatalytic degradation.
[0061] In order to explore the stability and recyclability of the composite catalyst, the 0.3-Ni4P2@NU-1000 after catalytic degradation of TMX was subjected to multiple cycle degradation experiments. Figure 8As shown in the figure, it can be seen that the composite catalyst 0.3-Ni4P2@NU-1000 still exhibits excellent degradation efficiency after the fifth photocatalytic cycle degradation. In order to further demonstrate that the catalyst has good structural stability, 0.3-Ni4P2@NU-1000 after the fifth photocatalytic cycle was subjected to XRD, FT-IR and SEM analysis. The results are shown in Fig. 9 (a)-(b), Fig.10 As shown in the figure, it can be seen that the peak shape and intensity of the composite catalyst 0.3-Ni4P2@NU-1000 are still very good, the FT-IR spectrum has no obvious changes, and the elements of the catalyst after recycling are evenly distributed, indicating that the crystal structure of the catalyst remains intact and the chemical structure has not changed, proving that 0.3-Ni4P2@NU-1000 has good recyclability and chemical stability.
[0062] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a polyacid-supported MOFs composite catalyst, characterized in that: The steps include: Disperse Zr salt and benzoic acid in N,N-dimethylformamide, heat at 100°C for 1h, add H4TBAPy and trifluoroacetic acid to the reaction solution, mix well, react at 100°C for 18h, and after the reaction, centrifuge and wash the reaction solution to obtain NU-1000; Under stirring conditions, an aqueous solution of Ni(OOCCH3)2 is slowly added to a mixed solution of Na2WO4·2H2O and Na2HPO4 to obtain a mixture; the mixture is refluxed for 2.5 hours, and after filtering the precipitate, K(OOCCH3) is added to the filtrate to obtain Ni4P2-POM; NU-1000 was added to the aqueous solution of Ni4P2-POM, and the mixture was reacted at 25°C for 72 hours under stirring to obtain a composite catalyst.
2. The preparation method according to claim 1, characterized in that: The ratio of the content of Ni4P2-POM in the aqueous solution of Ni4P2-POM to the added amount of NU-1000 is (1-5):
1.
3. The preparation method according to claim 1, characterized in that: The ratio of the mass of Zr salt, the mass of benzoic acid, and the volume of N,N-dimethylformamide is 0.098 g:2 g:8 mL.
4. The preparation method according to claim 1, characterized in that: The ratio of H4TBAPy mass to trifluoroacetic acid volume was 0.04 g:40 μL.
5. The preparation method according to claim 1, characterized in that: The ratio of solute mass to solvent volume in the aqueous solution of Ni(OOCCH3)2 is 5.5g:50mL.
6. The preparation method according to claim 1, characterized in that: The pH of the mixed solution is 7.
0.
7. The preparation method according to claim 1, characterized in that: The mixed solution is obtained by dissolving 33 g of Na2WO4·2H2O and 1.57 g of Na2HPO4 in 100 mL of water.
8. The preparation method according to claim 1, characterized in that: The added amount of K(OOCCH3) is 4g.
9. A composite catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The composite catalyst has a regular hexahedral rod structure and a specific surface area of 392.59-690.79m 2 / g, total pore volume is 0.2150-0.3646cm 3 / g.
10. Use of the composite catalyst as claimed in claim 9 in the photocatalytic degradation of pesticide organic pollutants.
Citation Information
Patent Citations
Pesticide residue degradation agent and preparation method thereof
CN116941612A